VD_FINDINFO ML / 2013 / 67 vom 11. Februar 2013 - VD Tribunal cantonal (2013)
DÉPENS, REPRÉSENTATION, ÉQUITÉ, RÉPARTITION DES FRAIS | 106 al. 1 CPC (CH), 107 al. 1 let. a CPC (CH), 107 al. 1 let. c CPC (CH), 107 al. 1 let. e CPC (CH), 95 al. 1 let. b CPC (CH)